Changes in microbial populations during co-composting of dewatered sewage sludge with pruning wastes in windrow piles - amirhossein nafez; mahnaz nikaeen; akbar hassanzadeh; safoora kadkhodaei (Society for Indonesian Biodiversity, 2020)
Abstract. Nafez AH, Nikaeen M, Hassanzadeh A, Kadkhodaei S. 2020. Changes in microbial populations during co-composting of dewatered sewage sludge with pruning wastes in windrow piles. Biodiversitas 21: 4648-4655. The aim of this paper was to study the composting of sewage sludge (SS) and pruning waste as bulking agent with regard to abiotic factors and succession of functional microbial groups. To prepare the composting piles bulking agent and SS in volumetric ratios of 1:1 (TW1), 2:1(TW2), and 3:1(TW3) were used, and a pile of raw sludge was used as control. Samples for investigation were obtained from the composting piles at time intervals of 5-7 d. The temperature of the control pile and TW1 was just 37°C and did not reach the thermophilic phase. The number of thermophilic bacteria increased to 14 log CFU gDW-1 in the thermophilic phase. The salmonella was lost on the 47th and 19th days of the composting process, for TW2 and TW3, respectively. There was a significant correlation between mesophilic fungi with mesophilic bacteria (r=0.942, P<0.001). The majority of the microbial populations inspected revealed their maximum numbers towards the end of the thermophilic phase, with decreasing tendencies afterward. The number of evaluated microorganisms was controlled by differences in physicochemical parameters at different composting phases. The results revealed that the scheduling of the thermophilic period, as well as the microbial community and environmental situations, affects the microbial structure andTW2 had the best quality compared to other piles in achieving the best thermophilic phase and elimination of pathogenic microorganisms.